Organizational Resilience and Sustainability of Small and Medium Enterprises in the Philippines - CARPIZO, RUBEN; Balila, Jolly; Mutia, Tilfemar (12th International Scholars Conference 2025, 2026)
The purpose of this study is to determine the relationship of organizational resilience and sustainability of Small and Medium Enterprises (SMEs) in the Philippines. The study used a descriptive-correlational research design. Validated survey questionnaires were distributed to 400 managers and owners of SMEs in the Philippines. The collected data were analyzed using mean, standard deviation, and regression. The results showed that the organizational resilience and sustainability of SMEs in the Philippines were very high. Moreover, the study also found that organizational resilience is a significantly related to SMEs sustainability (r = 0.510) in the Philippines with a p-value of 0.001. When organizational resilience and sustainability are analyzed using regression analysis, organizational resilience is a predictor of sustainability with an R square value of 0.226 and a p-value of 0.001.